(untitled) (Dhaka University Journal of Science, 2016)
Treatment of dyeing wastewater containing reactive Brilliant Orange H2R and Brilliant Red M5B dyes were investigated by using electrocoagulation process. The experimental results were analysed in terms of percent removal of dye with time. Electrocoagulation of dye containing wastewater was carried out in a two-electrode monopolar electrocoagulation cell using iron as sacrificial anode and 0.01 M NaCl as internal electrolyte in which the electrolyte concentration was maintained constant during the experiment. In electrocoagulation the effects of concentration of dye and applied current strength on dye removal efficiency were tested and found that both have significant effects on the electrocoagulation of dye from wastewater. Dhaka Univ. J. Sci. 64(2): 153-156, 2016 (July)